Association between Chronic Psychological Stress, Cortisol Dysregulation, and Risk of Breast Cancer Development in Women. A Case Control Clinical Study - HAMZA, MUHAMMAD; NAEEM, USAMA; ATHAR, SAMEEN; AFZAL, HAMNAA; NIAZI, AYESHA FATIMA; ASLAM, JAVERIA; ABBAS, MUHAMMAD UMAR; ABBAS, AIMEN (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Chronic psychological stress has been seen as a more and more probable factor in the development of cancer via its impact on the hypothalamic-pituitary-adrenal (HPA) axis and dysregulation of cortisol. Nevertheless, there is limited evidence among clinical populations (especially in low- and middle-income nations). Objectives: To assess the relationship between chronic psychological stress and cortisol dysregulation and the risk of breast cancer in women. Methods: The present study is a hospital-based case-control study, comprising of 47 women with a newly diagnosed, histologically confirmed breast cancer and 47 age-matched healthy women, as controls. A structured proforma was used to record the sociodemographic variables, reproductive history and exposure to chronic stress. The Perceived Stress Scale (PSS-10) was used to measure psychological stress. Cortisol levels in the morning went through tests of chemiluminescent immunoassay and evening cortisol in a subset was taken to determine the diurnal rhythm. Dysregulation of cortisol was characterized by abnormal morning cortisol and/or flattened morning to evening cortisol ratio. The statistical tests were chi-square, independent t-test and multivariate logistic regression. Results: PSS scores were much higher among breast cancer patients than they were among controls (24.8 vs. 17.2, p < 0.001). The cases were much more likely to have high psychological stress and long-term stressors in life. The mean morning cortisol levels were greater in cases (19.6 3g/dl) compared to controls (14.2 3g/dl) and cortisol dysregulation was more common in cases (61.7 vs. 27.6, p < 0.001). Multivariable regression demonstrated stress (AOR: 3.84) and dysregulated cortisol (AOR: 4.46) to be high predictors of breast cancer. Conclusion: Cryptic psychological stress and dysregulation of cortisol are both of significant relevance in risking breast cancer. The stress and endocrine imbalance screening can be used to detect women who are at high risks and aid the preventive measures.